A Dictionary of Quotations and Proverbs About Cats and Dogs - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2001)
Keywords: Cats; Quotations; maxims; etc; Quotations; maxims; etc; Dogs; dept.ils; dept.mat; faculty_collection

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00177 tex.type: [object Object]
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

The transition from paper to electronic journals: Key factors that affect scholars' acceptance of electronic journals - Kim, Hak Joon (Serials Librarian, 2001)
The primary purpose of this paper is to investigate what factors crucially affect scholar's acceptance of e-journals. Before reviewing various aspects of e-journals, it is necessary to fully understand the traditional journal system, because the developments, roles, and deficiencies of the paper journal system will illustrate some basic requirements for successful e-journals. This article also examines the developments of e-journals and presents a comprehensive examination of the economic, technological and cognitive, and sociological aspects of e-journals based upon an extensive literature review. With regard to the economic and technological and cognitive aspects, the benefits of scholarly e-journal publishing appear to be, by and large, favorable to the transition from paper to electronic journals. However, the major stumbling block is the credibility of scholarly e-journals. Whether or not scholars can obtain the same recognition or rewards through e-journal publication as they obtain through paper journal publication must be one of the key factors that affect scholar's acceptance of e-journals.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-081-770-161-36X tex.type: [object Object]
Keywords: Electronic journals; Journal functions; Journal system; Scholarly communication; Scientific reward system; dept.ils

A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-713-030-974-661 tex.type: [object Object]
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-574-806-615-498 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found